Optimizing digital online training satisfaction to grab digital online training business opportunity in the pandemic challenge - Afriansyah Yus Jazak; Anton Wachidin Widjaja (President University, 2022)
Several researches concluded roles of training including increasing the efficiency and compatibility of staff with the environment and consequently, improving service quality. Create job satisfaction and reduce conflict and disobedience, reduce absenteeism rates, other unnecessary costs and accidents, help improve individual performance and organizational effectiveness, develop talent, improve staff morale, facilitate the achievement of organizational goals. In the new normal conditions triggered by the COVID-19 pandemic which has occurred for more than 1 year in Indonesia, this also has an impact on training and learning activities so that the company transfers all training activities that are normally done face-to-face in class, replaced with digital and online training. This research is designed to see the relationship between the dimensions of online training participant satisfaction with online training referrals by participant to recommend the training to other employees to get online training business opportunities. This research was conducted through two methods in stages. The first one uses the exploratory method and continues by using the descriptive method. As the result of this research there is a significant relationship between the Online Training Dimension and Participant Training Satisfaction and Referral Training optimized to get greater opportunities to answer online training needs for companies, especially during the pandemic. This study has limitations, namely, research is only carried out under the ongoing Covid 19 pandemic, and research is carried out on a population of online training participants who attend training with a typical method.